Sociodemographic and Clinical Profiles of Patients Admitted in Tertiary Level Pediatric Hospital of Nepal: An Observational Study - Anil Kumar Shrestha; Santosh Adhikari; Sushil Gyawali; Bal Mukunda Basnet; Sobi Lal Maharjan; Pujash Karmacharya; Deepak Raj Paudel (Journal of Nepal Medical Association)
Introduction: Child health is crucial in low and middle-income countries. Pediatric healthcare in tertiary-level hospitals addresses complex medical conditions. This study aimed to describe the sociodemographic and clinical profiles of pediatric patients admitted to Kanti Children’s Hospital in Nepal. Methods: An observational cross-section study was conducted including all the inpatients under 15 years of age. The data were collected from the hospital medical record section from July 17, 2023 to July 15, 2024, after the ethical approval from Institutional Review Review Committee, (Reference number 2168). The statistical analysis included descriptive statistics to assess demographic characteristics, case types, admission patterns, and outcomes using Microsoft Excel and Statistical Package for Social Sciences (SPSS) 2024. Results: A total of 9682 pediatric cases were included, of which 6389 (65.99%) of the patients were male, with 3305 (34.13%) being aged 1 to 5 years. Among the admitted patietns 2194 (22.66%) had respiratory cause and 1520 (15.70%) had infectious disease. Mortallity rate was 203 (2.09%) and it was 82 (12.06%) in pediatric intensive care unit and 48(10.62%) in neonatal intensive care unit. Conclusions: Respiratory and infectious diseases were the most common cause of admission in pediatric settings with a higher prevalence in younger children. The majority of cases were residing outside the capital city. This study highlighted higher mortality rates in critical care units.